仁 (HUMANITY), 義 (RIGHTEOUSNESS), 禮 (PROPRIETY), 智 (WISDOM), 信 (TRUSTWORTHINESS) FROM THE PERSPECTIVE OF TRADITIONAL MORALITY - Pham, Ngoc Ham (VNU Journal of Foreign Studies, 2025)
With over 2300 years of feudal rule in China, a series of behavioral standards for each member of the family and society were established in this country. Five traditional moral standards, generally called the Five Constants, include humanity, righteousness, propriety, wisdom, and trustworthiness. These qualities have been the educational goals from family to school and serve as measures of a person’s value. Five traditional moral standards are also found in Vietnam and other countries like Japan and Korea, which are deeply influenced by Confucian thought. To this day, humanity, righteousness, propriety, wisdom, and trustworthiness remain core values. In this article, based on a semiotic perspective combined with cultural studies, an attempt is made to discuss the concepts of humanity, righteousness, propriety, wisdom, and trustworthiness embedded in Chinese characters 仁 (humanity), 義 (righteousness), 禮 (propriety), 智 (wisdom), 信 (trustworthiness) to offer a deep understanding of their semantic meanings and cultural implications. This will contribute to the education of traditional morality for the young generation.